Acupuncture-like transcutaneous electrical nerve stimulation as an accelerating tool for the recovery of the tissues exposed to vocal overload - Fuentes, Christopher Hernan; Arrau Bordalí, Javiera; Pino Quiroz, Gabriela; Valdivia Alarcón, Nataly; Aguilar Pavez, Camila (Revista de Investigación en Logopedia, 2020)
Traditionally, it has been suggested that rest is the ideal tool to allow natural recovery of tissues induced by overload. However, the times necessary for this to occur are very long. It has been estimated that electrotherapy is useful when it comes to recover some overused tissues, however, these benefits in vocal function are unknown. The purpose of this study was to describe the effects of acupuncture-like transcutaneous electrical nerve stimulation on the laryngeal and cordal tissues that were previously subjected to vocal overload. In this research, 21 women without pathology or vocal training participated, whose age was 24 ± 1.28 years. The participants were subjected to vocal overload for 40 minutes and subsequently to 15 minutes of acupuncture-like transcutaneous electrical nerve stimulation. Through continuous laryngoscopy, acoustic-perceptual analysis and symptomatic study, the changes caused by electrotherapy were examined. The main results include perilaryngeal and intrinsic laryngeal muscles relaxation, and elimination of the symptoms suffered. This way it is concluded that electrostimulation is a useful tool in the acceleration of tissue recovery subjected to vocal overload.